The use of non-steroidal anti-inflammatory drugs among soccer players in West Africa: A knowledge, attitude and practice survey with the elite in Republic of Benin - Nigan, I. B.; Kiki, S. M. D.; Gouthon, P.; Messan, F.; Tonon, B. A.; Nigan, R. Y. B. N. (Biology of Exercise, 2019)
Using anti-inflammatory leads to sometimes have undesirable side effects, although they can be freely purchased in stores and on the streets in West Africa countries. This study aims at determining the levels and relationships between knowledge, attitude, and practice of non-steroidal anti-inflammatory drugs (NSAIDs) among Beninese Elite soccer players. It is a cross-sectional study that uses the Knowledge, Attitude, and Practice survey of 233 Elite soccer players. Levels of knowledge and attitude in relation to NSAIDs use were low among 61.8% and 75.1% of the players, respectively, while 65.7% of them use the medications responsibly. The association between attitude and practice was significant (÷2 = 3.56; p = 0.04; Cramer`s V = 0.12), but the relation between the level of knowledge and level of attitude was not significant (p > 0.05), as was not that between the level of knowledge and practice regarding the use of NSAIDs (p > 0.05). Contrary to conventional wisdom, a low level of knowledge of NSAIDs was not associated with the misuse of these drugs. These results suggest that Beninese Elite soccer players have to improve their knowledge and attitude, regarding the use of NSAIDs to reduce the risk of side effects of these medications.